2016
DOI: 10.1016/j.ijsu.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticogastrostomy has advantages over pancreaticojejunostomy on pancreatic fistula after pancreaticoduodenectomy. A meta-analysis of randomized controlled trials

Abstract: The meta-analysis showed a significant difference between PG and PJ on PF: PG was associated with significantly less PF when compared to PJ, indicating that PG is superior to PJ for reconstruction after PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
3
23
2
Order By: Relevance
“…[5,6] According to the studies examined here, the POPF-related mortality rate was not statistically different between PJ and PG groups (1.0% vs. 0.8%; P  = .856; Table 1), nor did the overall mortality rate differ (2.2% vs. 2.2%; P  = .999). The superiority of PG compared with PJ in decreasing the mortality rate was one of the main topics examined in 16 systematic reviews and meta-analyses that have been carried out until now [1732] ; 14 confirmed our findings that there were no differences in the overall PO mortality rate, [18–20,2232] while 2 reported a lesser overall PO mortality rate for PG with respect to PJ. [17,21] He et al, [21] in particular, found a lesser mortality rate for PG with respect to PJ (2.6% vs. 7.1%, P  < .00001) in 22 observational clinical studies examining 3199 patients included in their systematic review and meta-analysis.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…[5,6] According to the studies examined here, the POPF-related mortality rate was not statistically different between PJ and PG groups (1.0% vs. 0.8%; P  = .856; Table 1), nor did the overall mortality rate differ (2.2% vs. 2.2%; P  = .999). The superiority of PG compared with PJ in decreasing the mortality rate was one of the main topics examined in 16 systematic reviews and meta-analyses that have been carried out until now [1732] ; 14 confirmed our findings that there were no differences in the overall PO mortality rate, [18–20,2232] while 2 reported a lesser overall PO mortality rate for PG with respect to PJ. [17,21] He et al, [21] in particular, found a lesser mortality rate for PG with respect to PJ (2.6% vs. 7.1%, P  < .00001) in 22 observational clinical studies examining 3199 patients included in their systematic review and meta-analysis.…”
Section: Discussionsupporting
confidence: 77%
“…[32] Seven reviews reported that there was a lesser incidence of B-C POPF Grades for PG with respect to PJ. [21,24,25,27,29,31,32] The lesser POPF rate after PG was not, however, associated with a lesser overall PO mortality rate, and none of the reviews provided information on the direct POPF-related mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the incidence of POPF, investigators have attempted various strategies, including the refinement of surgical techniques [13][14][15][16], application of adhesive materials around pancreatic enteric anastomosis site [17,18] and intravenous administration of agents, which inhibit pancreatic secretion [19][20][21]. However, most of these attempts failed to show remarkable superiority in preventing POPF, ultimately leading to no significant reduction in the incidence of POPF over the last three decades [17,19,[21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, PG is theoritically less demanding and has lesser liability to ischemia and more protection to the anastomosis due to the acidic nature of the gastric secretion which prevents activation of the pancreatic enzymes. 3 The anatomical location of the stomach nearby the pancreatic remnant enables tension-free anastomosis. 4 Tailoring the extent of posterior gastrostomy incision according to that of the pancreatic stump facilitates sufficient invagination of the pancreatic remnant inside the stomach and eliminates the problem of discrepancy between the size of the pancreatic remnant and the jejunal circumference that PG was introduced clinically by Waugh and Clagett in and evolved through several modifications.…”
Section: Introductionmentioning
confidence: 99%